Uji Aktivitas Antibakteri Ekstrak Propolis Lebah Trigona Incisa terhadap Bakteri Klebsiella pneumonia dan Staphylococcus aureus - Saleng, Annizah; Syafrizal, Syafrizal; Sari, Yanti Puspita (Jurusan Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, 2016)
Propolis is one of natural products produced honey bees and has frequently used as a drug or supplements, antiinflammation, therapy disease, accelerated healing cuts and others. In addition, propolis has many benefits one having the nature as an antibacterial. This study aims to establish the nature of bees antibacterial propolis Trigona incisa against bacteria Klebsiella pneumonia and Staphylococcus aureus. The ektraksi done in a maceration and the antibacterial with the diffusion discs kirby-bauer. The antibacterial activity it uses random design complete (RAL) consisting of 12 treatment and test 3 for every type of bacteria. Variation concentration the treatment is DMSO (control negative), 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 100% and kloramfenikol (control positive). Antibacterial test extract propolis bees Trigona incisa against bacteria Klebsiella pneumonia and Staphylococcus aureus, showed potential as antibacterial. The best to extract propolis construction beehive Trigona incisa in pursuing the growth of bacteria Klebsiella pneumonia is 70 % with broad zone obstruent formed the 11,18 mm (category strong) while bacteria Staphylococcus aureus does not hinder (weak) category. On wrapping bee products Trigona incisa, a weakling now under inhibit bacterial growth Klebsiella pneumonia and Staphylococcus aureus.